2012
DOI: 10.2174/138920112798868566
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin: an Agent Derived from Saffron for Prevention and Therapy for Cancer

Abstract: Cancer is one of the leading causes of death in the United States and accounts for approximately 8 million deaths per year worldwide. Although there is an increasing number of therapeutic options available for patients with cancer, their efficacy is time-limited and non-curative. Approximately 50-60% of cancer patients in the United States utilize agents derived from different parts of plants or nutrients (complementary and alternative medicine), exclusively or concurrently with traditional therapeutic regime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
115
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(118 citation statements)
references
References 39 publications
1
115
0
2
Order By: Relevance
“…Scientific studies have confirmed the validity of saffron extracts in the treatment of mild to moderate depression [5,6], and agent against erectile dysfunction [7], and as anti-arrhythmic agent and restorer of cardicac functions [8,9]. Other studies showed a role of saffron as a protector against age related macular degeneration [10,11], in reducing cognitive decline in patients with Alzheimer Disease [12,13], and as a source for potential anti-cancer agents [14,15,16].…”
Section: Introductionmentioning
confidence: 93%
“…Scientific studies have confirmed the validity of saffron extracts in the treatment of mild to moderate depression [5,6], and agent against erectile dysfunction [7], and as anti-arrhythmic agent and restorer of cardicac functions [8,9]. Other studies showed a role of saffron as a protector against age related macular degeneration [10,11], in reducing cognitive decline in patients with Alzheimer Disease [12,13], and as a source for potential anti-cancer agents [14,15,16].…”
Section: Introductionmentioning
confidence: 93%
“…Crocetin inhibits the growth of cancer cells through the inhibition of nucleic acid synthesis, induction of the antioxidative system, apoptosis, and hindering growth factor signaling pathways. 123 Crocetin was shown to inhibit LPS-induced nitric oxide release, reduce the levels of TNF-α, IL-1β, and intracellular ROS, activate the NF-κB pathway, and prevent LPS-induced hippocampal cell death. 124 Crocetin and its derivatives were found to have anti-proliferative effect in MCF-7 and MDA-MB-231 breast cancer cells in a dose-dependent manner.…”
Section: 73mentioning
confidence: 99%
“…128 Besides cell growth reduction, crocetin-derived compounds including crocin, safranal, and picrocrocin, displayed apoptotic activity. 123,129 Previous studies demonstrated that Zingiber officinale Roscoe (Zingiberaceae) as one of the important plant species that possessed an inhibitory effect on ovarian cancer cell growth through the inhibition of NF-κB activation, and reduced VEGF and IL-8 secretion. 130 Gingerol is the active secondary metabolite of Z. officinale.…”
Section: 73mentioning
confidence: 99%
“…Certain bioactive phytocomponents have been known for their anticancer properties. Some of these include curcumin, genestein, resveratrol, lycopene, rosemarinic acid and sulforaphane (Gutheil et al, 2011). Cyperaceae represents a family of monocotyledonous sedges with grassy resemblance.…”
Section: Introductionmentioning
confidence: 99%